HUKUM SYARAâ€™ DAN FIQH MENURUT WAHBAH AZ-ZUHAILI - Nofiardi, Nofiardi (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2011)
In Rasulullahâ€™s period, all law problems in many direct life aspect can be leaned to him. For example, when a moslem has some problems, that thing -problems- can be asked to rasululullah, and rasul answer it with the law based on sharia that demoted by Allah. But, after rasulullah death -up to now, sharia often be a problem for the moslem. Often sharia positionâ€™s -that actually is guide principal source lives in islam- shows dimness in law problem. Then, itâ€™s necessary to have a continual study towards this problem -in â€œmeaning ofâ€ and sharia â€œproblemâ€. Now there a kind of difficulty inclination in islam people to distinguish between sharia and fiqh. Even, oftentimes there meaning fusion between both of them. Here, author will study singly sharia definition and fikih to clarify this dimness. Then new at see position both -where sharia and fikih must present- and this article focus to wahbah az-zuhailiâ€™s opinion, with compare to other religious teachers opinion.